Dopamine - Dunnett, S. B. (Stephen B.) (Handbook of chemical neuroanatomy ;, 2005)
Dopamine is a major neurotransmitter of the brain involved in the control of movement, emotion, and cognition; disturbance in dopamine function is associated with disorders like Parkinsons disease, schizophrenia and attention deficit hyperactivity disorder. This volume of the Handbook of Chemical Neuroanatomy provides a series of in depth critical reviews of our present understanding of the most important aspects of dopamines organisation and disturbed function in the animal and human brain.